ONLINE CONSUMER REVIEW AND BEAUTY INFLUENCER ON COSMETICS PURCHASE INTENTION OF INDONESIAN FEMALE CONSUMERS - Rabiah, Arbi Siti; Rita; Parashakti, Ryani Dhyan; Mahfud, Imam; Adha, Shultonnyck (Journal of Business, Management, and Accounting, 2019)
In modern times women's lifestyles experience a lot of changes. Cosmetics are unique products because in addition to having the ability to meet women's basic needs for beauty, they also become a means for consumers to clarify their identity socially in the eyes of society. Nowadays cosmetics seem to be a primary need for some women. The results of this study provide information that online customer reviews do not have a significant and negative effect of -0.111, while beauty influencers have a significant and positive effect of 0.345. Online customer reviews and beauty influencers have a significant simultaneous effect on Maybeline's buying interest in Jakarta